Association of Stimulation and Sleep Duration with Developmental Outcomes in Children Aged 12–36 Months: - - Purnama Sari, Yulia; Ningtyas, Woro Setia; Puspitasari, Dwiyanti; Meinar Sari, Gadis (Rifa'Institute, 2026)
Introduction: Early childhood development during the golden years is crucial for future quality of life, yet developmental disorders remain a significant challenge. In Surabaya, Gundih Health Center showed the lowest coverage of developmental monitoring services. Objective: This study aimed to analyze the relationship between stimulation provision and sleep duration with developmental outcomes in children aged 12-36 months at Gundih Health Center, Surabaya. Method: A quantitative analytical study with cross-sectional design was conducted from April to September 2025. Using purposive sampling, 110 children aged 12-36 months were selected. Data were collected through questionnaires adapted from the Maternal and Child Health Book for stimulation assessment, Brief Infant Sleep Questionnaire for sleep duration, and Developmental Pre-Screening Questionnaire for developmental assessment. Data analysis employed univariate and bivariate analysis using Spearman rank correlation test. Result and Discussion: Results showed that 48.2% of children had age-appropriate development, while 51.8% demonstrated questionable development or possible deviations. Statistical analysis revealed a significant relationship between developmental stimulation and child development (p=0.034, r=0.202), indicating that better stimulation correlated with appropriate developmental outcomes. However, no significant relationship was found between sleep duration and child development (p=0.323, r=0.095). Conclusions: Developmental stimulation significantly influences child development outcomes, while sleep duration does not show a direct significant relationship with developmental progress in children aged 12-36